Terapi Murottal dengan Akupresur terhadap Tingkat Kecemasan dan Kadar Gula Darah pada Pasien dengan Penyakit Jantung Koroner - Farid Hajiri; Sri Endang Pujiastuti; Joni Siswanto (Jurnal Keperawatan Silampari, 2019)
The purpose of this study was to determine the effect of murottal and acupressure combination therapy on anxiety levels and blood sugar levels in patients with coronary heart disease, as well as describing the level of anxiety and pre and post blood sugar levels in the administration of combination therapy and non-combination therapy, and analyze the effect and differences in therapy combination and non-combination of anxiety and blood sugar levels. This study was a paired comparative analytic study using an experimental design with a control group pretest posttest design. Significant results in the Anova repeated measurement test on anxiety levels obtained p value <0.05 which means there is a significant influence of murottal and acupressure on anxiety levels, on blood sugar levels p values> 0.05 which means there is no significant effect of murottal and acupressure on blood sugar level. Conclusion, combination therapy between murottal with acupressure for 2x15 minutes a day is more effective in reducing anxiety of coronary heart patients in measurement 1 and measurement 2. Murottal therapy with acupressure and murottal therapy has no effect on blood sugar in measurement 1 and measurement 2. Keywords: Acupressure, Blood Sugar Levels, Anxiety, Al-Qur'an Murottal, Coronary Heart Disease